Inventory Turnover and Leverage's Impact on Financial Performance (Case Study of Cement Sub-Sector Companies Listed on the IDX) - Manurung, Agustina Dian Putri (Jurnal Akuntansi, Manajemen dan Ekonomi, 2023)
The purpose of this study is to ascertain how leverage and inventory turnover affect the financial performance of companies in the cement subsector listed on the IDX from 2017 to 2021. Leverage and inventory turnover are the independent factors in this investigation. Financial performance serves as the study's dependent variable. Companies in the cement subsector that were listed on the IDX between 2017 and 2021 make up the research population. As a method for research sampling, total sampling is used. While the type of data used is secondary data, which is obtained through the documentation technique by visiting the websites www.idx.co.id, and the websites of each company. Multiple linear regression analysis is the method of data analysis performed. A strong negative impact of leverage on a company's financial performance is shown via studies on hypothesis testing. Yet, there was no impact on financial performance for the inventory turnover variable.